Ultrasonography as Aid for Early Pregnancy Diagnosis in Zebu Cattle in a Natural Mating Programme - Galicia, L. L. (2006)
To utilise ultrasonography in Zebu cattle to test early pregnancy, multiparous Bos indicus COWS (n=74) were allocated with 2 mature Brahman bulls, which were replaced with new ones every four weeks. COWS were bled for radioimmunoassay progesterone analysis at the time of ultrasound and four days prior 07' after this event. The efficiency of the ultrasound findings and progesterone levels were compared wit' Kappa index using the computer programme (WIN) EPISCOPE. Ultrasound precision for early pregnancy diagnosis was 96%. Moreover, animals not clearly defined as pregnant, following examination revealed that only 54% were actually pregnant. The efficiency to detect the lack of ovarian activity was only 25% as revealed by progesterone concentrations lower than lngl ml. In contrast, the association between a detectable CL by ultrasound and progesterone values higher than lnglml was 90%. The incidence of embryonic death was 15.4%. Based on these results the efficacy for detecting early pregnancy by ultrasound and the presence of an active CL is satisfactory, whereas the precision to detect non-cycling animal is questionable and the incidence of embryonic death is high.